Variasi Morfologi dan Kelimpahan Kepiting Uca spp. di Kawasan Mangrove, Tuban-Bali - Krisnawati, Yuli; Arthana, I Wayan; Dewi, Ayu Putu Wiweka Krisna (Journal of Marine and Aquatic Sciences; Vol 4 No 2 (2018), 2017)
Fiddler crabs ( Uca spp.) are one of the mangrove fauna that has an important role of food chain within the scope of mangrove, which is as a deposit eater. The mangrove area in Kampoeng Kepiting has been damaged due to reclamation for Bali Mandara toll road construction, which can interfere the survival/existence of Fiddler crabs. Therefore, it is necessary to do a research concerning the abundance of Fiddler Crabs in Kampoeng Kepiting mangrove area. The aim of this study is to determine the type and abundance of Fiddler crabs and to discover the coherency among Fiddler Crabs abundance in the manner of c-organic matter content in Kampoeng Kepiting area. Fiddler crabs samples were carried out using 1×1 meter quadrant transect by digging as deep as 30 cm. The abundance of Fiddler crabs was analyzed under the Krebs equation. The results from this study indicate Fiddler crabs were found in Kampoeng Kepiting area ,i.e. Uca demani, Uca coarctata, Uca dussumieri, Uca bellator, Uca lactea perplexa, Uca tetragonon, Uca chlorophthalmus crassipes, Uca lactea annulipes, Uca triangularis, and Uca vocans . The highest Fiddler crabs abundance were found at station 4 which is 72±4,2 ind/m 2 , whilst the abundance of Fiddler crabs ( Uca spp.) at station 5 is (33±1,2 ind/m 2 ). The c-organic matter content has a strong relationship with the abundance of Fiddler crabs in Kampoeng Kepiting mangrove area (r = 0,91). This study shows that mangrove conditions in Kampoeng Kepiting are still able to support Fiddler Crabs ( Uca spp.) existence.